Sinister Wisdom : a journal of words and pictures for the lesbian imagination in all women. (Lincoln : Sinister Wisdom, 1977)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Box 30541, Lincoln, Nebraska 68503, vanaf (1980) 15 ; PO Box 660, Amherst, MA 01004
Periodiek